Study on the use of Typha spp. for the phytotreatment of water contaminated with ibuprofen - Dordio, Ana (2012)
Several studies on phytotoxic effects caused by organic xenobiotics and their removal from water by macrophytes have already been performed to evaluate the usefulness of these plants for phytoremediation technologies. In this context, a study was conducted to assess Typha spp.’s ability to withstand and remove, from water, the non-steroidal anti-inflammatory drug ibuprofen. For an initial ibuprofen concentration of 20 mgL 1, Typha removed nearly 60% of it within the first 24 h, attaining over 99% removal by the end of the assay (21 days). Exposure to higher ibuprofen concentrations did affect Typha’s growth but, by the end of the assays, plants’ growth as well as photosynthetic pigments approached normal values. An alteration in antioxidant enzymes activities (superoxide dismutase, catalase, guaiacol peroxidase) indicated that both roots and leaves were affected by the xenobiotic. Eventually, Typha seemed able to cope with ibuprofen’s induced oxidative damage suggesting its ability for phytotreatment of waters contaminated with ibuprofen.